Penentuan Derajat Esterifikasi Dengan Metode Base Line Pada Sintesis Aldimin Kitosan Asetat Melalui Reaksi Esterifikasi Dari Aldimin Kitosan Dengan Asetat Anhidrida - Churohma, Mifta; Tarigan, Daniel; Akkas, Erwin (JURNAL ATOMIK, 2017)
Determination degree of esterification with the baseline on the synthesis method aldimine chitosan acetate by esterification of aldimine chitosan with acetic anhydride has done. In this research, chitosan modified by chemical being aldimine chitosan acetate. Synthesis aldimine chitosan acetate produced by the esterification reaction between aldimine chitosan with acetic anhydride. The result of FT-IR analysis of aldimine chitosan acetate showed in wavenumbers 3448.72 cm-1, which indicated stretching vibration hydroxyl group -OH. Vibration absorption wave numbers 1735.93 cm-1 indicated carbonyl group C = O, ester and backed group C-O-C with wavenumbers 1033.85 cm-1. vibration absorption in wavenumbers 1651.07 cm-1 indicated the presence of C = N. Degree of esterification or degree of acetylation (DA) in aldimine chitosan acetate assign value 82.85%.